Konsep Pendidik dan Peserta Didik dalam Perspektif Pendidikan Islam - Asep Setiawan; Betty Mauli Rosa Bustam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The phenomenon of education today is that educators do not interact well with students. One example is educators who only explain subject matter from the beginning of class to the end of class without providing stimulus or response to their students. So that students become bored and learning objectives are not achieved. This research aims to describe the concept of educators and learners in the view of Islamic Education. The method used in this research is library research. The results of the study showed that educators are responsible not only for transmitting academic knowledge, but also for being moral role models, guiding students in character development, and integrating Islamic teachings into daily life. Islamic education emphasizes the importance of character education that includes moral values, ethics, and spirituality so that students become individuals who obey God and have noble morals. Thus, close collaboration between educators and learners in an Islamic education environment is expected to form individuals who are not only academically intelligent but also have noble character and spirituality.